Methionine Hydroxy Analog Supplementation to Increase Feed Utilization for Indigenous Sheep - Prasetiyono, Bambang Waluyo Hadi Eko; Mulyono, Mulyono; Widiyanto, Widiyanto (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2020)
In the tropical area such as in Indonesia, ruminant productivity is relatively low due to, among others, the low quality of nutrition that leads to low-efficiency metabolism at the level of ruminal fermentation, post rumen digestibility, and intermediary metabolism. This study was conducted with the objective to analize effect of methionine hydroxyl analog (MHA) supplementation on ruminal fermentation profiles of Indigenous sheep specifically in the increase of ruminant productivity. In vitro utility test was conducted using rumen fluid of the indigenous sheep and sample of ration having a proportion of grass and concentrate of 30%:70%, on dry matter basis. The treatments were three levels of MHA supplementation; T0: 0%, T1: 3%, and T2: 6% of dry matter (DM) concentrate. Variables measured were dry matter digestibility (DMD), organic matter digestibility (OMD), production of VFA, NH3, as well as total protein, and molar proportion of partial VFA of rumen fluid. Data were analyzed using analysis of variance (ANOVA) in a completely randomized design (CRD). The 6% MHA supplementation increased OMD with the highest production of total protein from 28.57 mg/g (T0) to 40.49 mg/g (T2) (P<0.05). Meanwhile, the lowest ratio of acetate : propionate was from 2.74 (T0) to 2.33 (T2) (P<0.05). It can be concluded that supplementation of MHA up to 6% in the concentrate increases the performance of Indigenous sheep ruminal fermentation and feed utility.